2014
DOI: 10.2176/nmc.oa.2013-0287
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Subaxial Cervical Pedicles by Using Three-Dimensional Computed Tomography Reconstruction Image

Abstract: Malpositioning of cervical screws risks neurovascular injury. A cervical screw fixation system can provide proper rigidity, alignment correction, and high rates of fusion afforded by high pullout biomechanical strength. The objective is to assess the dimensions and axis of the C3–C7 cervical pedicles. A 1-mm slice thickness computed tomography (CT) scan of the cervical spine of 30 patients (15 males, 15 females) were analyzed and reconstructed in three-dimensions using Mimics® 10.01 software. We measured pedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
(27 reference statements)
0
9
1
Order By: Relevance
“…In our study we that found morphometric parameters were significantly larger in men compared with women, and no significant differences were noted between left-and right-sided measured pedicle parameters at any spinal levels, which was in accordance with previous studies in other ethnic groups. 12,13,23,24 PW, PH, and PTA values in our study were found to be smaller than those in European/American, Thai, and Chinese populations. 12,13,24 An optimum of 4.5 mm PW is required for safe CPS placement in order to have 0.5 mm of bone stock on each side.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…In our study we that found morphometric parameters were significantly larger in men compared with women, and no significant differences were noted between left-and right-sided measured pedicle parameters at any spinal levels, which was in accordance with previous studies in other ethnic groups. 12,13,23,24 PW, PH, and PTA values in our study were found to be smaller than those in European/American, Thai, and Chinese populations. 12,13,24 An optimum of 4.5 mm PW is required for safe CPS placement in order to have 0.5 mm of bone stock on each side.…”
Section: Discussioncontrasting
confidence: 78%
“…Al-saeed et al 30 noted in an Arab population that PAL was 32.2 mm at C3, 32.3 mm at C4, 33 mm at C5, 33.5 mm at C6, and 34 mm at C7. Wasinpongwanich et al 23 noted in the Thai population that PAL was 29.10 mm at C3, 30.48 mm at C4, 32.05 mm at C5, 33.40 mm at C6, and 34.36 mm at C7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations